EASEMENT: STAGES OF DEVELOPMENT - Abdulkhaeva Anisa Abdumalikovna (TADQIQOTLAR, 2025)
Abstract: In this article, the author examines the legal nature of an easement (the right of limited use of someone else’s land). As one of the institutions of civil law. The stages of easement development from well-known land forms to the form of easement in the digital space are studied. The most important phases of development are regarded: Roman law, the unification of easements in civil laws of the XIX-XX centuries, their adaptation to the realities of the industrial period. Due to the emergence of new regulatory objects in the Internet space, the author pays attention to changes in the easement and easements of legal relations in this environment. In the end, the author’s conclusion and suggestions on how to improve this institution in modern realities are given.